Using the documentary “I’msaving myself for when carnival comes” and reflections on the world of work in a sociology lesson sequence: an experience report (Olhar de Professor, 2025)
This experience report presents the outcomes of a sequence of three sociology classes taught to first-year students in a Fashion Production technical program integrated with high school education. The lessons aimed to foster critical reflections on the world of work, using the Brazilian documentary "I'm Saving Myself for When  Carnival Comes" (2019) as the primary teaching resource to explore the sociological concepts of "work," "alienation," and "labor flexibility. "Filmed in Toritama, Pernambuco - known as the "jeans capital" - the documentary portrays the lives of local workers and their complex relationship with carnival. As a culminating activity, students wrote letters addressed to Toritama's residents, reflecting on the labor-related concepts discussed in class while engaging with the realities depicted in the film.Filmed in Toritama, Pernambuco - known as the "jeans capital" - the documentary portrays the lives of local workers and their complex relationship with carnival. As a culminating activity, students wrote letters addressed to Toritama's residents, reflecting on the labor-related concepts discussed in class while engaging with the realities depicted in the film.
Keywords: Documentary and the world of work; Sociology teaching; Labor flexibility; Case study